Healthy Mobile Check-In Study: Barriers to exercise for women in high and low SEP suburbs in Brisbane. (30th September 2020) - Carroll, J A; Rodgers, J; Lyons-Reid, J; Bennett, R
Abstract: Previous studies have demonstrated that physical activity (PA) promotes health and reduces risk for non-communicable diseases. However, 55% of Australian women did not meet the recommended levels of PA in 2018-19. There remains a gap in knowledge regarding the individual, household, and neighbourhood barriers to physical activity between women from high and low socioeconomic suburbs. We conducted a mixed-methods study to ascertain subjective accounts of the socioecological reasons for different daily logistics, travel, and PA between these groups. In addition to daily mobility data collated from GIS iPhone apps, in-depth interviews were held with 16 women from the high (Ashgrove) and low (Durack) SEP suburbs in Brisbane. Interview data was analysed at the individual, social, and environmental levels to unearth resistance to PA via these thematic strata. Individual psychological barriers to being active that were unique to low SE suburbs included the 'lack of enjoyment' gained from PA. Both high and low SE suburbs reported being 'time poor'. For low SEP participants, this was driven by financial demands, and for high SEP participants, this was driven by work demands. Both groups reported being burnt out. Individual physical barriers for both groups included sore joints, injury, pelvic pain and weight. Social barriers unique to participants from a high SE suburb included 'opportunities to exercise socially', and 'mother guilt'. Both groups reported 'family responsibilities' as a social barrier. Neighbourhood changes that could increase PA in the low SEP suburb included facilities to increase walkability. Participants from the high SE suburb were largely satisfied with the state of their neighbourhood. This study provides foundational insight into improved public health strategies for increasing levels of PA amongst women in Brisbane from different SEP groups. Our findings support the idea that a combination of broad strategies and a targeted approach is needed. Key messages: Women from high and low socioeconomic suburbs experience different barriers to physical activity. Health promotion strategies need to accommodate this to improve overall health and reduce inequality. Women from high and low socioeconomic suburbs face psychological, physical and social barriers to exercise. Broad health promotion strategies and a targeted approach is required to address barriers.